Doing Climate Justice: Theological Explorations - Collet, Jan Niklas; Gruber, Judith; Jong-Kumru, Wietske de; Kern, Christian; Pittl, Sebastian; Silber, Stefan; Tauchner, Christian (Religion and Transformation in Contemporary European Society, 2022)
The struggle against the climate crisis and for a livable future on earth raises profound questions of justice that call for theological engagement. Anchored in concrete situations of climate vulnerability and responsibility, this volume investigates the theological epistemologies, practices and imaginaries that have profoundly shaped climate politics in the past and explores possible theological reformulations that can open up sustainable and just futures. With these critical and constructive theological reflections inspired by Liberation Theology, it seeks to contribute to practices of climate justice by inspiring the development of socially and economically just ways of living in global, interspecial community.